Extraction of Cantharidin from Mylabris phalerata Pallas with Compound Enzyme and HPLC Analysis - Ge, Xizhen; Du, Xiaoxia; Yu, Yan; Xin, Xin; Tian, Pingfang (Asian Journal of Chemistry, 2012)
Cantharidin is a monoterpene anhydride released from beetle Mylabris phalerata Pallas or Mylabris cichorii Linnaeus as a defensive substance showing versatile pharmacological activities especially anticancer. Now efficient extraction methods for cantharidin have been established so far. Here, four extraction methods, including hydrochloric acid, NaOH solution, mixed extraction and compound enzyme (cellulase and pectinase) methods were compared with traditional Chinese pharmacopoeia extraction method. A quantitative HPLC method was developed for the estimation of cantharidin in Mylabris phalerata extract. The compound enzyme method was revealed to present the highest yield of cantharidin among these methods, followed in order by hydrochloric acid method, mixed extraction method, Chinese pharmacopoeia method and NaOH solution method. The HPLC conditions comprise: diamonsil C18 (250 mm × 4.6 mm, 5 μm), flow rate of 1.0 mL/min, detection wavelength of 273 nm, column temperature at 25 ºC, mobile phase with acetonitrile: water = 40:60. Under these conditions, cantharidin could be well extracted from Mylabris phalerata.